2000
DOI: 10.1128/jvi.74.17.7997-8002.2000
|View full text |Cite
|
Sign up to set email alerts
|

Detachment of Human Immunodeficiency Virus Type 1 from Germinal Centers by Blocking Complement Receptor Type 2

Abstract: After the transition from the acute to the chronic phase of human immunodeficiency virus (HIV) infection, complement mediates long-term storage of virions in germinal centers (GC) of lymphoid tissue. The contribution of particular complement receptors (CRs) to virus trapping in GC was studied on tonsillar specimens from HIV-infected individuals. CR2 (CD21) was identified as the main binding site for HIV in GC. Monoclonal antibodies (MAb) blocking the CR2-C3d interaction were shown to detach 62 to 77% of HIV ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
51
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 26 publications
5
51
1
Order By: Relevance
“…In other experiments examining FDC-mediated maintenance of HIV infectivity, we found that FDCs were unable to maintain virus infectivity in vitro unless specific Ab to determinants present on the virus envelope was present (Burton et al, unpublished). These results contrast with other studies in which HIV binding to FDCs appears to be dependent on adhesion molecules (CD54, CD11a) (25) or complement protein C3 or its fragments (26,27). However, it should be noted that in one of the latter studies, the presence of specific Ab did increase virus trapping on FDCs (26).…”
Section: Figurecontrasting
confidence: 55%
“…In other experiments examining FDC-mediated maintenance of HIV infectivity, we found that FDCs were unable to maintain virus infectivity in vitro unless specific Ab to determinants present on the virus envelope was present (Burton et al, unpublished). These results contrast with other studies in which HIV binding to FDCs appears to be dependent on adhesion molecules (CD54, CD11a) (25) or complement protein C3 or its fragments (26,27). However, it should be noted that in one of the latter studies, the presence of specific Ab did increase virus trapping on FDCs (26).…”
Section: Figurecontrasting
confidence: 55%
“…Interestingly, complement receptors were also shown to play a role in the capture and docking of virus on the surface of uninfected follicular DCs in germinal centers (32,33). However, CR2 rather than CR1 and CR3, was shown to be the main binding molecule for opsonized HIV on follicular DCs (34).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of the generation of C3d fragments, released HIV binds efficiently to CR2-expressing cells, which facilitates the B cell-mediated transmission of opsonized HIV to T cells. This fI-mediated sequential processing of C3 fragments from C3b to C3d on the surface of HIV is likely to have in vivo relevance since C3d-coated viruses are predominantly found on FDC in germinal centers, which represent by far the largest viral reservoir in HIV-infected individuals (4,5,7).…”
mentioning
confidence: 99%
“…HIV bound extracellularly to the follicular dendritic cells (FDC) 3 in germinal centers of lymph nodes represent by far the largest viral reservoir in HIV-infected individuals (5,6). The binding of this infectious pool of HIV in the germinal centers depends mainly on interactions of complement receptor type (CR) 2 expressed on FDC (or B cells) with C3d fragments on the viral surface (4,7). In addition, an association of complement-opsonized HIV with peripheral B cells through CR2-C3d interactions was described in HIV-infected individuals (8).…”
mentioning
confidence: 99%